2022
DOI: 10.1038/s41598-022-21458-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a catechins-enriched diet associated with moderate physical exercise in the prevention of hypertension in spontaneously hypertensive rats

Abstract: Hypertension represents the main risk factor for the onset of cardiovascular diseases. Pharmacological treatments to control hypertension have been associated with new treatments involving physical activity and/or the intake of natural components (nutraceuticals). We here report the effects produced by a combination of a natural component (catechins) and a moderate exercise program on the development of hypertension in spontaneous hypertensive rats compared with those of each individual treatment. Arterial blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Previously, we observed that physical activity and a diet enriched with antioxidants individually have an important hypotensive effect, and the association showed a more prolonged, but not better, hypotensive effect than the single treatment ( Del Seppia et al, 2022 ). In the present descriptive study, we assessed the effects of a physical exercise program associated with a diet enriched with products based on Annurca apple polyphenolic fraction ( Maisto et al, 2022 ) on preventing microvascular damages due to cerebral hypoperfusion and reperfusion injury in spontaneously hypertensive rats (SHRs) in association or when administered alone.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previously, we observed that physical activity and a diet enriched with antioxidants individually have an important hypotensive effect, and the association showed a more prolonged, but not better, hypotensive effect than the single treatment ( Del Seppia et al, 2022 ). In the present descriptive study, we assessed the effects of a physical exercise program associated with a diet enriched with products based on Annurca apple polyphenolic fraction ( Maisto et al, 2022 ) on preventing microvascular damages due to cerebral hypoperfusion and reperfusion injury in spontaneously hypertensive rats (SHRs) in association or when administered alone.…”
Section: Introductionmentioning
confidence: 84%
“…The present data collected in the same animals used in Del Seppia et al (2022) confirmed that in adult SHRs, arterial hypertension is accompanied by marked microvascular changes as previously described by Bobik (2005). In fact, under baseline conditions, prior to cerebral hypoperfusion and reperfusion injury, the pial microcirculation of adult SHRs presented several alterations, such as more conspicuous fluorescent dextran leakage, indicating increased permeability and increased formation of ROS, accompanied by a decrease of the perfused capillary length, when compared with the young SHRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also should be noted that other pathways contribute to the metabolism of 20-HETE, including CYP2C, alcohol dehydrogenase, lipoxygenase, cyclooxegenase, glucuronosyltransferase, and β-oxidation pathways [ 4 ]. Additionally, the antioxidant effect of CAT in SHR may play a role in its antihypertensive effect [ 15 ]. These findings indicate that CAT lowers blood pressure in SHR by different mechanisms, and the modulation of AA metabolism in the kidney is one of them.…”
Section: Discussionmentioning
confidence: 99%
“…Catechin (CAT), in Figure 1 , is a natural flavonoid that is abundant in plant-based foods, especially cocoa. A substantial body of evidence demonstrates a wide spectrum of the therapeutic benefits of catechin, including cardioprotection and chemopreventive effects [ 14 , 15 ]. The study was undertaken to investigate the antihypertensive effect of CAT in young male spontaneously hypertensive rats following sub-chronic oral administration and to assess the effect of CAT administration on the metabolism of arachidonic acid in the kidney, with a particular focus on sEH and CYP4A.…”
Section: Introductionmentioning
confidence: 99%